2021
DOI: 10.3389/fcell.2021.746194
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NREP Promotes Migration and Invasion in Gastric Cancer Through Facilitating Epithelial-Mesenchymal Transition

Abstract: Graphical Abstract(A) Study Flow chart, (B) Diagram depicting the regulation mechanism of NREP in the tumorigenesis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…NREP is highly expressed in embryo and mouse brain, and can participate in cell proliferation, migration, differentiation and other biological functions (Pan et al, 2002;Yao et al, 2015). NREP plays an important role in the progression of malignant tumors and may be involved in the activation of cancer-related fibroblasts and epithelial-mesenchymal transition (EMT), both of which are mediated by transforming growth factor-β1 (Liu et al, 2021). In addition, Liu et al (2021) reported that the expression of NREP was positively correlated with the Frontiers in Genetics frontiersin.org abundance of M2 macrophages, which are potent immunosuppressors, suggesting that NREP is overexpressed in GC and affects the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…NREP is highly expressed in embryo and mouse brain, and can participate in cell proliferation, migration, differentiation and other biological functions (Pan et al, 2002;Yao et al, 2015). NREP plays an important role in the progression of malignant tumors and may be involved in the activation of cancer-related fibroblasts and epithelial-mesenchymal transition (EMT), both of which are mediated by transforming growth factor-β1 (Liu et al, 2021). In addition, Liu et al (2021) reported that the expression of NREP was positively correlated with the Frontiers in Genetics frontiersin.org abundance of M2 macrophages, which are potent immunosuppressors, suggesting that NREP is overexpressed in GC and affects the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The M2 polarization of macrophages has been confirmed to promote the progression of malignant tumors. 34 , 35 In addition, Akt and STAT6 have been reported to promote M2 polarization. 36 , 37 In the present study, exosomes overexpressing LOC441178 inactivated Akt/STAT6 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining followed the method described in our previous study [ 30 ]. Staining was examined by epifluorescence microscopy (model BX60-32FB2-A03; Olympus Corp.), and different filters were used for capturing images using an Olympus DP50 camera.…”
Section: Methodsmentioning
confidence: 99%